Towards a Typology of Zero Aboutness: Expletive A in Fornese and Chiru in Cilentano - De Cia, Simone; Cerullo, Mariangela (Languages (Basel), 2024)
This paper investigates the syntactic–pragmatic behavior of two expletive-like elements, namely a and chiru, in Fornese and Cilentano, two Romance varieties spoken in Northern and Southern Italy, respectively. We argue that a and chiru are not bona fide expletive subjects but discourse-pragmatic expletives, which mark zero aboutness or the absence of an aboutness referent in an utterance. The investigation of Fornese and Cilentano points towards the existence of a sub-class of null-subject languages where aboutness as a discourse feature must be structurally satisfied by merging an overt or null topic in the syntactic spine of the clause. In the absence of such an element—for example, in thetic clauses—a discourse-pragmatic expletive is externally merged as a last-resort strategy to satisfy [uAboutness]. We argue that, in these null-subject languages, the satisfaction of the discourse feature [uAboutness] is an LF requirement, which is subject to a parametric choice. We show that, in Fornese, “default” [aboutness] is satisfied in SubjP, which is the canonical syntactic position for overt subjects within a cartographic approach. In Cilentano, on the other hand, [aboutness] is satisfied in a higher position within the C-domain, namely ShiftP, the canonical syntactic position that hosts overt aboutness/shift topics.